Cycling a Lithium Metal Anode at 90 °C in a Liquid Electrolyte - Hou, Li‐Peng; Zhang, Xue‐Qiang; Li, Bo‐Quan; Zhang, Qiang (Angewandte Chemie International Edition, 2020)
Stable operation at elevated temperature is necessary for lithium metal anode. However, Li metal anode generally has poor performance and safety concerns at high temperature (>55 °C) owing to the thermal instability of the electrolyte and solid electrolyte interphase in a routine liquid electrolyte. Herein a Li metal anode working at an elevated temperature (90 °C) is demonstrated in a thermotolerant electrolyte. In a Li|LiFePO4 battery working at 90 °C, the anode undergoes 100 cycles compared with 10 cycles in a practical carbonate electrolyte. During the formation of the solid electrolyte interphase, independent and incomplete decomposition of Li salts and solvents aggravate. Some unstable intermediates emerge at 90 °C, degenerating the uniformity of Li deposition. This work not only demonstrates a working Li metal anode at 90 °C, but also provides fundamental understanding of solid electrolyte interphase and Li deposition at elevated temperature for rechargeable batteries. A Li metal anode working at 90 °C is demonstrated in a thermotolerant liquid electrolyte. The anode undergoes 100 cycles in a Li|LiFePO4 battery at 90 °C (10 cycles in a practical carbonate electrolyte). High operation temperature promotes independent and incomplete decomposition of Li salts and solvents to form a distinctive solid electrolyte interphase.